STUDI PERBANDINGAN PENGGUNAAN KARBON AKTIF TEMPURUNG KEMIRI DENGAN KARBON AKTIF KOMERSIAL DALAM SOLIDIFIKASI Cr(VI) - Yusie Rossita (Purifikasi, 2006)
This research compared the influence of composition variations of commercial and nutmeg shell activated carbons in solubilisation/stabilization (S/S) process of Cr(VI) artificial liquid waste. The dry weight variations of portland cement+fly ash and activated carbon were of 97%:3%, 94%:6%, 91%:9%. The S/S specimens were soaked in acetate buffer pH 2 solution with time variations of 0, 7, 14 and 28 days. Research data showed that activated carbon, could decrease the Cr(VI) leaching until ±70,5% and increased the compressive strength. The use of nutmeg shell activated carbon showed better performance of S/S products than those of commercial activated carbon. The weight composition variations in every type of activated carbon used, did not influence the compressive strength test results and leachability of Cr(VI). Addition of 3% of activated carbon represented the most economical composition with acceptable results of Toxicity Characteristic Leaching Procedure (TCLP) and compressive strength tests.